Review: Chitin and Chitosan from Shellfish Wastes (Journal of Science and Technology, 2016)
Chitin, a polymer of N-acetyl-D-glucosamine residue, currently obtained from crustaceans, and with a moisture content of 5-10%, total nitrogen content of 6.9%, and average molecular weight of 1.036 x 106 daltons, has traditionally been marketed in the form of flakes, powders, beads, gels, etc. It is widely distributed in nature and its quantitative importance in living beings is now well known. It is found in marine invertebrates, insects and fungi in association with proteins, calcium deposits and pigments, where it performs a protective and supporting role [2]. Considerable amounts of chitin are present in shellfish wastes. Chitosan, the N-deacetylated form of chitin forms the body wall of most fungi, molds and yeasts. Several studies have been carried out to investigate chitin chemistry, structure, modification and applicabilities and these have shown that, chitinous polymers have unusual combination of properties such as high-water binding capacity [4] and good film-forming properties [5] which make them useful in the food, cosmetics, pharmaceutical, paint and textile industries, agriculture, biotechnology, and in medicine. Both chitin and chitosan are now being produced in commercial quantities from crustacean wastes in Japan and to a relatively lesser extent in the United States [61. Chitosan is also being produced on a laboratory scale by deacetylation and fermentation of fungal cells [7]. In Ghana, chitin is being produced on a laboratory scale [11].